Peningkatan Kualitas Bacaan Al Qur'an Melalui Kegiatan Tahsin di Pondok Pesantren Putri Al Ikhlash Jember - Erlina, Lira; Rahma, Sabrur; albahiy, Rusyda; Choirunnisak, Choirunnisak; Zulaihah, Siti; Kurniati, Indi; Rani, Feni Mai; Rahman, Minnatur (Pusat Penelitian dan Pengabdian Masyarakat STIQ ZAD Cianjur, 2025)
Moldy boarding school in Indonesia that focuses in the field of tahfidz Al-Quran is no longer denied. Each Educational Center is competing in improving the quality of its learners in the focus of the intended field. Various methods dirangcang and applied in an effort to raise the quality of students who are educated. One of the methods used in some educational centers is the method of tahsin and talqin Al-Quran. This method is actually the method that our Prophet used in guiding his companions to keep the Quran. And this Journal discusses the influence of tahsin activities in improving the quality of reading santriwati Pondok Pesantren Putri Al Ikhlas Jember held by students of Kuliah Kerja Nyata (KKN) STIQ ZAD Cianjur.